Fostering learner autonomy and critical reflection through digital video-journals in a university foreign language course. Issue 2 (4th March 2019) - Villamizar, Andrés Gabriel; Mejía, Glenda
ABSTRACT: Many studies have documented the benefits of incorporating reflective journals into foreign language education at university level, though the pedagogic tendency has been to utilise these valuable learning resources to enhance students' written language skills. This study focuses on how the production of a digital reflective journal in video format can assist in the improvement of oral language abilities in tertiary students of Spanish as a foreign language. With spoken language as the driving vehicle for this assessment task, the course coordinator and educator in charge aimed to promote the development of learner autonomy and self-reflection. In addition, to foster students' agency in this process, the task incorporated the use of modern digital technologies, which are part of the repertoire of communication channels used by today's university language learners. Findings suggest that completing this self-reflection assessment task afforded creative teaching and learning experiences, and generated opportunities for learners to improve critical thinking skills, written language proficiency and oral communication. It also heightened their motivation to engage with language-related cultural knowledge, and minimised feelings of anxiety towards communicating verbally in a foreign language.